Audio Sculpting of Majeed Amjad’s Poetry - Ahmed, Sudheer; Abid, Nazar; Islam, Muneer ul (sourcecoder, 2023)
Poetic imagery is an artistic tool used by the poet to present his delicate thoughts which are created as a result of his poetic experience and observation. These images are being classified on the basis of different human senses. For example, such images have visual, auditory and tactile nature. In this article, the authors have carried out a crtical and analytical study of auditory images found in the poetic works of famous Urdu poet, Majeed Amjad while giving relevant poetic pharases from his various poems